Gagasan Pesantren Ramah Lingkungan: Respon Santri Akan Pentingnya Konservasi Lingkungan - Hariyanto, Hariyanto; Hariyanto, Arif (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2022)
One of the biggest challenges in maintaining the cleanliness of the cottage is the effectiveness of managing the cottage waste from upstream to downstream. This is important because the number of students who continue to grow also results in the amount of waste being produced. Environmental issues that often arise are related to environmental pollution or pollution, air pollution, air which takes a very long time to return to normal. Not only because of vehicle fumes but the lack of public awareness in caring for and protecting the environment, such as the use of environmentally friendly plastic. With the Qur'anic commandment to preserve the earth and not destroy it, pesantren institutions have the responsibility to understand the various effects of the existence of a pesantren complex and its students. The identity of Islamic boarding schools has been synonymous with simplicity as the main capital for environmentally friendly implementation. This is where the response of the santri and the attention of the pesantren in responding to various developments that occur with the environment.